Workplace Justice: Employment Obligations in International Perspective - Verge, Pierre (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "Workplace justice: employment obligations in international perspective," edited by H.N. Wheeler and J. Rojot.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; International; Labor; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z